Acute creatine supplementation enhances technical performance in adolescent basketball players under cognitive-motor dual-task condition - Junyu Wu; Peng Qiu; Youqiang Li (Journal of the International Society of Sports Nutrition, 2025)
Background Basketball games involve numerous cognitive-motor dual-task (CMDT) situations, where athletes must execute technical skills while processing complex on-court information. However, adolescent athletes often experience performance declines under CMDT conditions due to increased cognitive load. Creatine supplementation has been shown to enhance both physical and cognitive functions, but its acute effects on basketball skill performance under CMDT conditions remain unclear. This study investigates the impact of acute creatine supplementation on the technical performance of adolescent basketball players under single-task (ST) and CMDT conditions.Methods A randomized counterbalanced crossover design with a Latin square arrangement was used to recruit 40 male adolescent basketball players (13–14 years old) with provincial-level competitive experience. Participants received either creatine monohydrate (0.3 g/kg/day for 5 days, plus 0.1 g/kg pretest) or placebo, with a 4-week washout period between phases. To minimize learning and order effects, a standardized familiarization session was conducted prior to testing, and the sequence of ST and CMDT conditions was counterbalanced using a Latin square design. The CMDT condition required players to perform a continuous subtraction task while executing dribbling, passing, and shooting tasks. Performance metrics, subtraction task accuracy, heart rate, and ratings of perceived exertion (RPE) were collected. Two-way repeated measures ANOVA and paired t-tests were conducted for statistical analysis (α = 0.05, Bonferroni-corrected).Results Under CMDT conditions, creatine supplementation significantly improved performance in dribbling, passing, and shooting tasks (all p < 0.05), while only dribbling and shooting performance improved under ST conditions (p < 0.05). Dual-task cost significantly decreased in dribbling and passing (p < 0.05), but not in shooting (p > 0.05). Subtraction task accuracy improved only during shooting (p = 0.013). Additionally, creatine supplementation significantly reduced heart rate and RPE scores across all tasks and both conditions (p < 0.05).Conclusion Acute creatine supplementation enhances technical performance in adolescent basketball players under CMDT conditions, reduces physiological and psychological load, and supports its use as a short-term nutritional intervention to optimize game performance.